Methodical approaches of forming high-technological manufacturing on the basis of efficient functioning - Andreev, Oleg S. (Opción, 2019)
The article is aimed at researching the economic nature of management of formation and functioning of the special economic zones via review of scientific approaches to the development of the special economic zones as a method. As a result, the economic and social identification aspects are the most important aspects of the efficiency of developing special economic zones. In conclusion, development of science-intensive productions is influenced by a great number of factors, some of which can develop only with the support of the government.